Overcoming the dormancy in kudzu seed (Pueraria phaseoloides (Roxb.) Benth) - Zambrano Marcos, Abel (2019)
The kudzu seeds (Pueraria phaseoloides), a species of vital importance for the implementation of tropicalpastures in the jungle of Peru, they are characterized by latency and to overcome this problem,dierent types of scarication are recommended. The treatments studied to overcome latency in kudzuseeds were sulfuric acid (98 %), potassium nitrate (0, 2 %), sulfuric acid (98 %), potassium nitrate(0, 2 %), water, mechanical scarication (sandpaper) and one control with four repetitions, and 24experimental units, each experimental unit consisted of 400 seeds. In this investigation, 2400 kudzuseeds in germination tests and the datawere analyzed in a completely randomized design (CRD) withthe corresponding analysis of variance (ANVA) and for the comparison of means, the Tukey test wasused at 0, 05. The statistical analyzes showed a high statistical signicance for the studied treatments,being the chemical scarication by means of the use of sulfuric acid (98 %) which showed satisfactoryresults in the rupture of the kudzu seed coat.